A Kickstart to Life: Australian Football League as a Medium for Promoting Lifeskills in Cape York Indigenous Communities - Dinanthompson, Maree; Sellwood, Juanita; Carless, Felicity (The Australian Journal of Indigenous Education, 2008)
Abstract This paper presents evidence collected from an evaluatory study of the Kickstart program conducted by Australian Football League (AFL) Cape York in far North Queensland. The aim of the study was to investigate the effectiveness of the Kickstart program in meeting its overall objective of enhancing lifeskills of Indigenous Australians through participation in AFL. Evidence collected via interviews with Indigenous youth, parents, teachers and Kickstart stakeholders (including community representatives) suggest mixed meanings surrounding the interpretation of “lifeskills”, and yet improvement in the education, attitudes and lifestyle choices of Indigenous youth in the selected Cape York communities.